2013
DOI: 10.1021/es401706m
|View full text |Cite
|
Sign up to set email alerts
|

Non-Targeted Analysis of Petroleum Metabolites in Groundwater Using GC×GC–TOFMS

Abstract: Groundwater at fuel release sites often contains nonpolar hydrocarbons that originate from both the fuel release and other environmental sources, as well as polar metabolites of petroleum biodegradation. These compounds, along with other polar artifacts, can be quantified as "total petroleum hydrocarbons" using USEPA Methods 3510/8015B, unless a silica gel cleanup step is used to separate nonpolar hydrocarbons from polar compounds prior to analysis. Only a limited number of these metabolites have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…The results of the present study indicate the value of conducting nontargeted analysis as part of some environmental investigations . Although traditional targeted analysis allows for tracking and quantification of specific compounds, it may tell only a partial story.…”
Section: Resultsmentioning
confidence: 66%
“…The results of the present study indicate the value of conducting nontargeted analysis as part of some environmental investigations . Although traditional targeted analysis allows for tracking and quantification of specific compounds, it may tell only a partial story.…”
Section: Resultsmentioning
confidence: 66%
“…The GC × GC also detected several of the 57 target polar metabolites that were not detected by the traditional GC at detection limits of 10 µg/L, further suggesting that the target polars identified by the GC × GC were present at single digit µg/L levels. A complete list of unique TICs from this study and additional details about the GC × GC‐MS analysis are presented in Mohler et al (in press). DOI: 10.1021/es401706m.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that these were likely biodegradation intermediates of petroleum hydrocarbons (Zemo and Foote ). Zemo et al (, ) argued on the basis of 760 tentatively identified degradation intermediates identified by Mohler et al () that the intermediates pose little to no risk in groundwater, but the issue remains controversial (Mohler et al. ; Brewer and Hellmann‐Blumberg ; ITRC ).…”
Section: Introductionmentioning
confidence: 99%